Changing Scenario of Household Consumption Pattern in Kerala: An Emerging Consumer State of India - P. Padma; E. V. Ramasamy; T. V. Muralivallabhan and A. P. Thomas (Soc Indic Res, 2018)
Sustainability is considered as a remedy for the environmental issues arising due to over consumption of natural resources. In this context, the general household consumption pattern in India and—one of its states—Kerala has been studied for a period of 50 years. Generally Monthly Per capita Consumer Expenditure (MPCE) is linked with consumption, disparities in consumption pattern among different sectors of the society and sustainability at large. This study is based on the data from National Sample Survey Organization, Government of India. The findings of this study indicate that the MPCE has gone up for India and Kerala during the study period. The state of Kerala has an increased MPCE than the country; the rate of increase is twofold for its rural sector and 1.5 fold for the urban sector. Increased consumption consequent to urbanisation has been found to be the cause for the change in consumption pattern of Kerala.